The Relationship Between Teachers' Self-Efficacy Regarding First Aid And Injury Management At SDIT Al Mumtaz West Kalimantan - Lince Amelia; Almumtahanah Almumtahanah; Hidayah Hidayah (CV. AFDIFAL MAJU BERKAH, 2026)
Injuries in school-aged children are a significant and frequent health problem in the school environment. Teachers, as first responders, play a crucial role in providing first aid to prevent further complications. However, teachers' self-efficacy in first aid and injury management remains a significant concern. The purpose of this study was to identify the relationship between teachers' self-efficacy regarding first aid and their injury management skills at SDIT Al Mumtaz, West Kalimantan. This study used a cross-sectional design with a sample of 62 teachers. Data collection was conducted using a valid and reliable questionnaire regarding self-efficacy and injury management skills. Statistical tests used descriptive statistics and the Spearman rank correlation test with a p-value of 0.05. Most teachers had moderate self-efficacy (61.3%) and fairly satisfactory injury management skills (65%). However, the correlation test showed no significant relationship between teachers' self-efficacy and injury management skills (p=0.418; r=-0.105). Self-efficacy is not the only factor that influences injury management skills. Improving teacher competency in administering first aid requires support through continuous training and practical experience so that self-efficacy evolves into consistent and effective capability.